Egitto, Iraq ed Etruria nelle fotografie di John Alfred Spranger : viaggi e ricerche archeologiche (1929-1936) - Anastasio, Stefano, (Archaeopress archaeology., 2019)
This volume presents the 1930s archaeological photo-albums of photos make it possible to understand, after almost a century, how many Egyptian, Mesopotamian and Etruscan sites appeared at the time of their first excavations.